2018
DOI: 10.1093/ijnp/pyx119
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nicotine Metabolism Ratio on [11C]-(+)-PHNO PET Binding in Tobacco Smokers

Abstract: BackgroundIdentifying the biological basis of smoking cessation success is of growing interest. The rate of nicotine metabolism, measured by the nicotine metabolite ratio, affects multiple aspects of nicotine dependence. Fast nicotine metabolizers tend to smoke more, experience more withdrawal and craving, and have lower cessation rates compared with slow metabolizers. The nicotine metabolite ratio predicts treatment response, and differences in brain activation between fast metabolizers and slow metabolizers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
(107 reference statements)
0
4
0
1
Order By: Relevance
“…Specifically, following cigarette smoking, a 12% to 15% reduction in D2 and D3 receptor binding potential was observed compared to control conditions [ 46 ]. These findings are likely influenced by genetics, where, during abstinence, slow metabolizers of nicotine had lower [ 11 C]PHNO-binding potential compared to fast metabolizers within the D2 regions of the striatum [ 47 ]. Interestingly, there was no change in [ 11 C]PHNO-binding potential in the striatum of nicotine-dependent individuals following the presentation of tobacco-associated cues [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, following cigarette smoking, a 12% to 15% reduction in D2 and D3 receptor binding potential was observed compared to control conditions [ 46 ]. These findings are likely influenced by genetics, where, during abstinence, slow metabolizers of nicotine had lower [ 11 C]PHNO-binding potential compared to fast metabolizers within the D2 regions of the striatum [ 47 ]. Interestingly, there was no change in [ 11 C]PHNO-binding potential in the striatum of nicotine-dependent individuals following the presentation of tobacco-associated cues [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…These differences, however, were not observed among participants without a history of smoking, underscoring the possible gene (fast vs. slow nicotine metabolism) Â environment (exposure to nicotine) interaction. In addition, PET imaging research by Di Ciano and colleagues (96) showed that slower metabolizers had fewer D2-type dopamine receptors than faster metabolizers, drawing a link between NMR and dopaminergic signaling. While further research is required to fully delineate the relationships between the NMR and brain circuitry, the existing evidence strongly suggests that personalized approaches have implications for smoking cessation treatments that extend beyond acute withdrawal.…”
Section: What Are Potential Mechanisms Through Which the Nmr May Operate To Personalize Smoking Cessation Treatments?mentioning
confidence: 99%
“…No differences were found in post-cigarette [ 11 C]-(+)-PHNO BP ND between fast and slow metabolizers. 21 However, this could be explained by a number of methodological differences between this study and our study including a less sensitive analysis method and a lengthy delay between cigarette smoking and PET scanning in the work by Di Ciano and colleagues. Fast metabolizers experience greater daily fluctuations in nicotine concentrations which may explain why they experience greater reward from smoking.…”
Section: Discussionmentioning
confidence: 79%
“… 52 , or no group differences in smoking-induced dopamine release, for example, Ref. 21 . The parameter presented herein, is analogous to BP ND in the literature because it evaluates the change in the level of dopamine binding.…”
Section: Discussionmentioning
confidence: 99%